Does dexamethasone suppress the ACTH response in preterm babies?. Issue 4 (April 1989) - Rennie, J M; Baker, B; Lucas, A
Abstract : Tests of adrenal stimulation with adrenocorticotrophic hormone (ACTH) were performed before and after commencing dexamethasone treatment in 12 infants. All except one of the tests performed showed the expected twofold rise in serum cortisol, suggesting that in this group of premature babies dexamethasone did not suppress the adrenal response.